The adoption of internet of things (IOT) on construction site - Chong, Wen Xin (2021)
The Internet of Things (IoT) is one of the main backbones in the fourth industrial revolution. IoT is an innovative technology and it carries huge advantages to most industries such as engineering, agriculture, medicine, etc. In recent years, the use of IoT is also penetrating into the construction industry. Due to covid-19 outbreak, construction sites have been impacted the most. The progress of the construction works has been seriously delayed, the health and safety of the construction workers on site are threatened as well as the site productivity has reached all-time low. How can the adoption of IoT mitigate the problems on the construction site? This research explores the current practices of IoT on the construction site, analyses the importance of IoT on construction site as well as evaluates the attitude of individual construction practitioners towards IoT adoption on construction site. The research method used is the quantitative method which collects data by using questionnaires. In order to design the questionnaire for data collection, a thorough literature review on the research scope has been carried out and a theoretical framework has been developed. The targeted respondents for this research are construction practitioners who work on the construction site for instance developers, consultants, contractors, sub-contractors, suppliers and specialists. A total of 300 questionnaires have been sent out, 117 questionnaires are returned and only 101 questionnaires are valid to be studied in this research. The research findings have revealed that the IoT adoption on construction sites is very low as there are only a few construction organisations that have already adopted IoT on construction sites. Overall, the construction practitioners especially those in their twenties have high agreement on the importance of the IoT on construction sites and have positive attitudes towards the IoT adoption on construction sites. This research is able to provide an insight on the current IoT adoption on the construction site and how IoT improves the construction site amidst this pandemic outbreak.